Haemin deprivation renders Bacteroides fragilis hypersusceptible to metronidazole and cancels high-level metronidazole resistance. (19th January 2022) - Paunkov, Ana; Gutenbrunner, Katrin; Sóki, József; Leitsch, David
Abstract: Background: Infections with Bacteroides fragilis are routinely treated with metronidazole, a 5-nitroimidazole antibiotic that is active against most anaerobic microorganisms. Metronidazole has remained a reliable treatment option, but resistance does occur, including in B. fragilis . Objectives: In this study we tested whether haemin, a growth supplement for B. fragilis in vivo and in vitro, had an influence on the susceptibility of resistant B. fragilis strains to metronidazole. We further tested whether haemin-deprived B. fragilis would be more susceptible to oxygen and oxidative stress. Metronidazole has been described to cause oxidative stress, which we argued would be exacerbated in haemin-deprived B. fragilis because the bacteria harness haemin, and the iron released from it, in antioxidant enzymes such as catalase and superoxide dismutase. Methods: Haemin was omitted from growth media and the effect on metronidazole susceptibility was monitored in susceptible and resistant B. fragilis strains. Further, haemin-deprived B. fragilis were tested for resistance to aeration and hydrogen peroxide and the capacity for the removal of oxygen. Results: Omission of haemin from the growth medium rendered metronidazole-resistant B. fragilis strains, including an MDR isolate from the UK, highly susceptible to metronidazole. Haemin deprivation further rendered B. fragilis highly susceptible to oxygen, which was further exacerbated in resistant strains. B. fragilis was incapable of scavenging oxygen when haemin was omitted. Conclusions: We propose that haemin deprivation overrules resistance mechanisms by rendering B. fragilis hypersusceptible to metronidazole due to a compromised antioxidant defence. Monitoring of haemin concentrations is imperative when conducting metronidazole susceptibility testing in B. fragilis .